Strategies of LncRNA DLX6-AS1 on Study and Therapeutics - Zhao, Yanyan; Li, Pei (Frontiers in Genetics, 2022)
Accumulating evidence has revealed the vital regulatory roles of lncRNA DLX6-AS1 in various tumors at pre-transcriptional, transcriptional, and post-transcriptional levels, which makes it a potential prognosis factor and therapeutic target. In addition, the presence of lncRNA DLX6-AS1 in the exosomes of peripheral blood of patients with tumors may also contribute to it being a possible cancer-related biomarker. However, most literature studies are devoted to studying the effect of lncRNA DLX6-AS1 as a sponging molecule of miRNAs, the research of which is likely to get stuck into a dilemma. Literature studies published already have demonstrated an exciting cell malignant phenotype inhibition with the knockdown of lncRNA DLX6-AS1 in various tumor cell lines. With the comprehensive development of delivery systems, high-throughput sequencing, and aptamers, the problems of finding novel research methods and exploring the therapeutic options which are based on lncRNA DLX6-AS1 in vivo could come into a period to deal with. This review aims to summarize the research statuses of lncRNA DLX6-AS1, discuss other study methodologies and therapeutic strategies on it, which might be of help to the deep learning of lncRNA DLX6-AS1 and its application from basic to clinical research.